Control of Bovine Leukemia Virus in Three US Dairy Herds by Culling ELISA-Positive Cows. (25th June 2019) - Ruggiero, Vickie J.; Bartlett, Paul C.
Abstract : The objective of this trial was to evaluate a test-and-cull approach to controlling bovine leukemia virus (BLV) in US dairy herds with a low BLV prevalence. Despite worldwide distribution of the virus, 21 nations have eradicated BLV from their dairy cattle and are currently considered 'BLV-free.' In contrast, the US has attempted no industry-wide BLV control programs and has experienced an increase in BLV prevalence among dairy cows to about 40%. This raises concerns about production efficiency, herd health, and sustainability. In a pilot field trial with three Midwestern-US dairy herds, a test-and-cull approach using ELISA screening of milk samples was successful in reducing BLV prevalence in two herds. In the third herd, BLV prevalence increased following the introduction of infected heifers that were raised at an out-of-state calf raising facility. This trial demonstrated that a test-and-cull approach to BLV control can be successful in US dairy herds with low BLV prevalence, but ongoing surveillance is necessary to prevent reintroduction of the virus.